Change characteristics of health-related quality of life and its association with post-stroke fatigue at four-year follow-up - Synne G. Pedersen; Audny Anke; Mari T. Løholm; Marianne B. Halvorsen; Marit Kirkevold; Guri Heiberg; Marte Ørbo; Oddgeir Friborg (Medical Journals Sweden, 2024)
Objective: To explore trajectories that describe change in post-stroke health-related quality of life with fatigue as outcome. Design: Observational and prospective study. Subjects: Stroke survivors (N = 144) with predominantly mild or moderate strokes. Methods: The multidimensional Stroke-Specific Quality of Life scale was used at 1 and 4 years, and the Fatigue Severity Scale at 4 years post-stroke. Latent class growth analyses were used as person-oriented analyses to identify meaningful trajectories. Socio-demographic and stroke-related covariables provided customary adjustment of the outcome, as well as prediction of class membership. Results: The latent class growth analysis models were estimated for "physical health", "visual-language", and "cognitive-social-mental" components of the Stroke-Specific Quality of Life scale, which extracted trajectories describing a variation in stable, deteriorating and improving functional patterns. The stable, well-functioning trajectory was most frequent across all components. More pronounced fatigue was associated with trajectories describing worse functioning, which was more prominent among females compared with males. Living alone implied more fatigue in the "cognitive-social-mental" component. Within the "visual-language" components' trajectories, younger and older participants reported more fatigue compared with middle-aged participants. Conclusion: Most participants belonged to the stable, well-functioning trajectories, which showed a consistently lower level of fatigue compared with the other trajectories.